Philip Morris international delivering a smoke-free future - launching a product in a highly regulated environment - Avondo, Timothy (2022)
The work project consists of a case study, teaching note and project evaluation report on Philip Morris International’s mission of delivering a smoke-free future. The case study presents the company’s transformation and introduces PMI’s next-generation product IQOS that is said to have the potential to be less harmful than conventional cigarettes. The teaching note focuses on the impact of regulators on heated tobacco products. The evaluation report analyzes and provides recommendations for PMI’s main challenges: widespread mistrust from stakeholders and lack of awareness for IQOS.